A Rare Case Report of Amiodarone-Induced Bone Marrow Granuloma - Sunpil Hwang; Sucheta Kundu; Karishma Kadariya; Brett Barlow (Annals of Internal Medicine: Clinical Cases)
Amiodarone has rarely been reported to induce bone marrow granulomas. In this case, we describe the case of a 67-year-old man who was incidentally found to have pancytopenia while receiving amiodarone therapy for 18 months. A bone marrow biopsy revealed noncaseating granulomas, presumably causing pancytopenia. Subsequently, amiodarone was withdrawn, resulting in a gradual improvement of the pancytopenia. The resolution of amiodarone-induced bone marrow granuloma and associated cytopenia is readily achievable through physicians’ awareness and appropriate discontinuation of the medication therapy. Consequently, we recommend considering amiodarone as a potential contributor to bone marrow granuloma and cytopenia.